Progress of research on the diagnosis and treatment of accessory parotid gland tumor - TIAN Liangliang, ZHAO Jiaxiong, NAN Xinrong (Editorial Office of Stomatology, 2024)
The accessory parotid gland is a normal salivary gland tissue completely separated from the main parotid gland, which is mostly located in the middle of the face. Any tumor originating from the parotid gland can occur in the accessory parotid gland. Due to the special location of the disease, the diagnosis and treatment of accessory parotid gland tumor is more difficult and more dangerous than that of the parotid gland tumor. This article reviews the anatomy and physiology, clinical diagnosis and treatment of accessory parotid gland tumors, in order to provide guidance for clinical diagnosis and treatment.